MARVELD2 (DFNB49) mutations in the hearing impaired Central European Roma population--prevalence, clinical impact and the common origin - Mašindová, Ivica; Šoltýsová, Andrea; Varga, Lukáš; Mátyás, Petra; Ficek, Andrej; Hučková, Miloslava; Sůrová, Martina; Šafka-Brožková, Dana; Anwar, Saima; Bene, Judit; Straka, Slavomír; Janicsek, Ingrid; et al. (PloS one, 2015)
BACKGROUND: In the present study we aimed: 1) To establish the prevalence and clinical impact of DFNB49 mutations in deaf Roma from 2 Central European countries (Slovakia and Hungary), and 2) to analyze a possible common origin of the c.1331+2T>C mutation among Roma and Pakistani mutation carriers identified in the present and previous studies. METHODS: We sequenced 6 exons of the MARVELD2 gene in a group of 143 unrelated hearing impaired Slovak Roma patients. Simultaneously, we used RFLP to detect the c.1331+2T>C mutation in 85 Hungarian deaf Roma patients, control groups of 702 normal hearing Romanies from both countries and 375 hearing impaired Slovak Caucasians. We analyzed the haplotype using 21 SNPs spanning a 5.34Mb around the mutation c.1331+2T>C. RESULTS: One pathogenic mutation (c.1331+2T>C) was identified in 12 homozygous hearing impaired Roma patients. Allele frequency of this mutation was higher in Hungarian (10%) than in Slovak (3.85%) Roma patients. The identified common haplotype in Roma patients was defined by 18 SNP markers (3.89 Mb). Fourteen common SNPs were also shared among Pakistani and Roma homozygotes. Biallelic mutation carriers suffered from prelingual bilateral moderate to profound sensorineural hearing loss. CONCLUSIONS: We demonstrate different frequencies of the c.1331+2T>C mutation in hearing impaired Romanies from 3 Central European countries. In addition, our results provide support for the hypothesis of a possible common ancestor of the Slovak, Hungarian and Czech Roma as well as Pakistani deaf patients. Testing for the c.1331+2T>C mutation may be recommended in GJB2 negative Roma cases with early-onset sensorineural hearing loss.
Keywords: exony; Connexin 26; Gene Frequency; Sequence Homology, Nucleic Acid; haplotypy; mutace; konexiny; efekt zakladatele; Connexins; Founder Effect; Slovenská republika; Slovakia; Genotype; Hearing Loss; Age of Onset; Infant; Česká republika; Exons; Roma; věk při počátku nemoci; MARVELD2 protein; prevalence; Haplotypes; sekvenční homologie nukleových kyselin; Pakistan; jednonukleotidový polymorfismus; Romové; Pákistán; Czech Republic; Maďarsko; frekvence genu; MARVEL Domain Containing 2 Protein; Polymorphism, Single Nucleotide; lidé; nedoslýchavost; Humans; kojenec; Prevalence; Hungary; genotyp; konexin 26; Mutation; Alleles; alely